Purpose-driven Organizations (Springer Nature, 2019)
A higher purpose is not simply about profit. Symbolising the motivations of our actions and efforts, it reflects something much more aspirational and contributes to our global society. This open access book offers novel solutions to ensure employees support a wider organizational meaning whilst guaranteeing that the company benefits from the employee’s individual sense of purpose. Advocating a shift from previous models and theories, this book contributes to debate and offers insight for both scholars and practitioners. The chapters bring together academic rigour and practical models to help readers distinguish between the fads and influential strategies. Exploring the development of purpose at each level of business, from strategy and leadership to communication, this book avoids theoretical jargon and provides new approaches to building sustainable purpose-driven organizations. This is an Open Access book sponsored by DPMC Spain, UIC Barcelona and Corporate Excellence - Centre for Reputation Leadership